Performance Evaluation of the RSUP Dr. M. Djamil Intersection, Jalan Perintis Kemerdekaan, Padang City - Veronika Salmi; Dzikra Marsa Esmara; Eko Prayitno; Risayanti (Universitas Putra Indonesia YPTK Padang, 2026)
Rapid growth in the number of vehicles in Padang City has caused traffic congestion at critical locations, one of which is the Dr. M. Djamil General Hospital (RSUP) intersection. Although equipped with traffic signal infrastructure, the intersection currently operates as an unsignalized junction because the traffic lights are not in use. This study aims to evaluate existing performance and propose alternative solutions based on the 2023 Indonesian Road Capacity Manual (PKJI). Primary data were obtained through field surveys conducted over four days during morning, midday, and evening peak periods. Analysis of existing conditions during the evening peak hour (Saturday, 17:00–18:00 WIB) revealed a degree of saturation (DS) of 0.89 and an intersection delay of 15.34 seconds/vehicle, corresponding to Level of Service C (stable flow, moderate density). Three alternative solutions were examined: installing traffic signals (3-phase), widening the major road combined with traffic signals, and widening the major road without traffic signals. Comparative results indicate that Alternative Solution 3 (widening the major road by 1 meter without traffic signals) is the most effective, yielding a DS of 0.87, a delay of 14.84 seconds/vehicle, and Level of Service B.